The effect of Marrubium vulgare L extracts against urinary tract bacteria pathogens infection in Alassaba’a hospital, of west Tripoli - abdusalam, Khaled; Ehmeda, Ahmed; Joumh, Duha; Allishani, Ghalih; Abozakhar, Mareen (Journal of Pure & Applied Sciences, 2024)
Urinary tract infections (UTIs) are common infections that happen by many types of bacteria. Some of bacteria have resistance against several types of antibiotics. Many medicinal plants used as an alternative treatment around the world. Marrubium vulgare L has been reported to exhibit several biological properties. Thus, the aim of current study is estimating antimicrobial activities of M. vulgare against Escherichia coli, Klebsiella pneumoniae and Staphylococcus aureus, which caused urinary tract infections, isolated from infected patients. In the results, the growth of all tested bacteria was inhibited strongly by methanol extract at 1.0% (w/v) with inhibition zones 11.00, 11.00 and 15.50 mm against E. coli, k. pneumoniae and S. aureus respectively. Besides, Minimum Inhibitory Concentration (MIC) values were ranged between 0.625 to 1.25 mg/mL. While, Minimum Bactericidal Concentration (MBC) values were ranging between 1.25 to 2.5 mg/mL. On the other hand, hexane extract also was inhibited the growth of E. coli, k. pneumoniae and S. aureus with inhibition zones 10.00, 11.00 and 12.50 mm respectively. In addition, MIC values ranging 2.5 mg/mL, while MBC values of 5 mg/mL against all bacteria. In conclusion, the methanol extract of M. vulgare had a strongly effects on all bacteria compared to hexane extract, thus it can be developed as anti-bacterial agent.